RELATIONSHIP OF AREA RATIO TO DISPLACEMENT ON SUBGRADE STABILIZED BY DEEP SOIL MIXING - Dara Ayu Lisna Hadi; Yulvi Zaika; As’ad Munawir (Rekayasa Sipil, 2022)
Expansive clay soil has high potential of swelling due to minerals content which bind water, therefore, soil improvement is required to stabilize the swelling behavior by add binder additive such as lime in deep soil mixing method (DSM). In this study, Finite Element model approach was performed with embankment provided on the top of expansive clay layer to provide bearing layer for road construction. As the deep soil mixing is applied on the subgrade (expansive clay layer), some model variation is performed such as diameter variation with 0.4m; 0.6m; 0.8m, depth variation with 5m; 6.5m; 8m and space variation 0.8 m;1.2m;1.6m; 2.4m. Area ratio parameter also used for ease understanding of deep soil mixing behavior with so many model variations provided. Analysis results shows that higher area ratio of deep soil mixing will provide lower displacement value either immediate displacement or consolidation displacement. Moreover, plot result of area ratio shows that area ratio of 0.4 provide effective value regarding consolidation displacement and duration.